The past and present of Cadiz and Turdetania in Strabo’s ‘Geography’: reflections on integration processes - dos Santos Silva, Bruno (Romanitas - Revista de Estudos Grecolatinos, 2023)
The process of integration in the Ancient Mediterranean represents a complex and multifaceted phenomenon, the contours of which are revealed by both archaeological and material sources. This article aims to reflect precisely on this process through an analysis of the work Geography by Strabo (1st century BC), describing Turdetania’s space and the city of Cadiz. With a detailed reading of book III of this work, it is intended to offer an alternative view of the role of the city of Cadiz, for Strabo and other contemporary written sources, in the transformations observed in the space of Turdetania. It is argued that, instead of being a paradigm for the study of Romanization, as some authors defend, both Cadiz and Turdetania can be understood as models of a world in integration long before the arrival of the Romans, with this city being a central agent of this process.